Social entrepreneurship : Theory and practice - Praskier, Ryszard, ....-; Nowak, Andrzej, ....- (Cambridge : Cambridge University Press, 2012)
Social Entrepreneurship: Theory and Practice is about the creative ways in which social entrepreneurs solve pressing and insurmountable social problems. Theories of social change are presented to help demystify the 'magic' of making an immense, yet durable and irreversible, social impact. Utilizing case studies drawn from various fields and all over the world, the authors document how social entrepreneurs foster bottom-up change that empowers people and societies. They also review the specific personality traits of social entrepreneurs and introduce the new kind of leadership they represent.
Keywords: Sociaal ondernemen